2014
DOI: 10.3354/ab00564
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influence on timing of parturition, fecundity, and larval quality in three shelf rockfishes (Sebastes spp.)

Abstract: Differences in maternal investment and reproductive timing can have important consequences for offspring survival. Prior studies on nearshore rockfishes have shown significant effects of maternal age and size on the timing of parturition, fecundity, and larval quality, offering advantages to population persistence by maintaining age diversity in rockfish populations. In this study, reproduction in chilipepper Sebastes goodei, widow rockfish S. entomelas, and yellowtail rockfish S. flavidus was examined to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…For example, it has long been recognized that some rockfish species, including Chilipepper, produce multiple broods, complicating efforts to accurately estimate annual fecundity (Beyer et al, 2015;Stafford et al, 2014). If the likelihood of multiple broods increases with female size or age, but is difficult to document (due to covariation with female condition, climate and the difficulties in identifying a secondary brood), then the relative reproductive contribution of females exhibiting such patterns may be underestimated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it has long been recognized that some rockfish species, including Chilipepper, produce multiple broods, complicating efforts to accurately estimate annual fecundity (Beyer et al, 2015;Stafford et al, 2014). If the likelihood of multiple broods increases with female size or age, but is difficult to document (due to covariation with female condition, climate and the difficulties in identifying a secondary brood), then the relative reproductive contribution of females exhibiting such patterns may be underestimated.…”
Section: Discussionmentioning
confidence: 97%
“…Although this stock was also estimated to be at low levels (just above 25% of the unfished level) during the late 1990s, it was assessed to be healthy in 2007, at around 70% of the unfished biomass. Although the 2007 assessment assumed constant Ф rel , Beyer et al (2015) and Stafford et al (2014) have recently reported a reasonably strong size-dependent Ф rel relationship. We used the 2007 model, updated to utilize the most recent stock synthesis software (Methot and Wetzel, 2013), to evaluate the differences in assessment results with and without a size-dependent Ф rel .…”
Section: Case Study: Assessments Of Eastern Pacific Rockfishmentioning
confidence: 98%
“…Previous research on rockfish parturition timing has found older females begin releasing larvae earlier in the season than younger females [ 17 , 21 , 22 ]. As such, we modelled larval OGV as a function of both maternal age and parturition timing.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates the importance of older and larger rockfish females disproportionately contributing to the productivity of these stocks. In many rockfish species, the older and/or larger females display increased relative fecundity (Beyer et al 2015), higher larval quality (Berkely et al 2004), and more protracted or earlier spawning periods (Sogard et al 2008;Stafford et al 2014). Additionally, larger rockfish potentially have larger energy reserves and therefore possess the ability to energetically support spawning during less-favorable environmental conditions (Schultz et al 2011).…”
Section: Maturity Of Deepwater Rockfishmentioning
confidence: 99%
“…Additionally, larger rockfish potentially have larger energy reserves and therefore possess the ability to energetically support spawning during less-favorable environmental conditions (Schultz et al 2011). The strength of maternal effects appears to vary among species, and it is important to identify species with strong maternal effects, as they may benefit from the protection of age structure (Stafford et al 2014). There is increasing evidence that the contribution of large or old females to the recruitment of rockfishes and other teleost species is significant, and fishery-mediated truncation of the size or age structure of these populations should be considered (Vallin and Nissling 2000;Beldade et al 2012;Hixon et al 2014).…”
Section: Maturity Of Deepwater Rockfishmentioning
confidence: 99%